SOLASODINE STEROID BIOCONVERSION BY MYCOBACTERIUM PHLEI DSM 43286. - S. Pudjiraharti; T. A. Budiwati; J. Kantasubrata; A. T. Karossi (Research Center for Chemistry - LIPI, 1992)
Bioconversion of solasodine by Mycobacterium phlei DSM 43286 was conducted to obtain intermediate compounds which might be used as precursor in the production of steroidal drugs, i:e androst-4-en-3, 17-dione (AD) and androsta-l,4-diene-3,17-dione (ADD). M. phlei was firstly grown in nutrient broth medium at 37 °C for 8.5 hours with agitation of 200 rpm. The bacterial culture thus obtained was used as starter to inoculate the conversion medium containing 0,02% solasodine as the substrate and 0.01% 8-hydroxyquinoline as inhibitor. Bioconversion was conducted for 12 days at 37 °C using the same speed of agitation. Analysis of the bioconversion products was carried oUl using samples taken periodically at a 24-hour interval by TLC and HPLC methods. TLC analysis using chloroform-ethyl acetate (80:20) as eluent, measurement of the nuvamum wavelength and molar extinction coefficient value showed that AD and ADD was not found in the fermentation product,, but other intermediau: compound might the present. However, HPLC analysis of the fermentation products using Ik'Porasil column and benzene- ethylacetatechloroform (40:80:10) as eluent, showed -peaks with retention time similar to that of AD (during the 2nd - 9th day of incubation) and, ADD (during the 5th - 6th day offermentation) and, other unknown peaks.